Levantamento dos custos do ciclo de vida de um sistema fotovoltaico residencial conectado à rede da COSERN - Silva, Lêdson Led Freitas da (Universidade Federal Rural do Semi-Árido, 2021)
This work performs a case study on the survey of the life cycle costs of a residential photovoltaic system connected to the network of COSERN located in the city of Mossoró, Rio grande do Norte, in order to address the possible costs related to the installation of the system until the end of its useful life, which are the initial costs, maintenance costs, replacement costs, energy and generation costs and disposal costs of the system. The solar irradiation data in the region were analyzed through meteorological data obtained from the CRESESB website, normative resources of the National Agency of Electric Energy (ANEEL) were used and equipment was chosen from the Brazilian market according to their technical data for the sizing of the photovoltaic system, considering that 137kWh is equivalent to 1kWp of the installed system and considering a loss of 25% of the system to determine the monthly generation. The technical analysis showed that the city of Mossoró has a great potential for generation due to its level of solar radiation and to meet the consumption profile of the consumer unit under study a system of 2.86kWp was dimensioned to compensate an average monthly consumption of 392.41 kWh, the system is composed of 8 monocrystalline modules of 400W of power, from the manufacturer Jinko Solar and a 3kW inverter, from the manufacturer Growatt. The project had an initial cost of R$19,960.80 for the acquisition of the equipment and all the necessary installation and a survey was made of the costs for 25 years in some specific years, the first, fifth, tenth, fifteenth, twentieth and twenty-fifth years to compare with the costs that would be without the solar system with the solar system in operation and a value of R$65,786 was obtained that would be paid without the solar system for 25 years and a value of R$9,179.90 with the solar system during the same years. It was concluded that, after raising the costs for economic evaluation, the implementation of this photovoltaic system presented itself as viable and compensated all the initial investment made, even with the maintenance and replacement costs during its useful life
Keywords: Levantamento; Custos; Geração; Dimensionamento; Survey; Costs; Generation; Dimensioning; ENGENHARIAS::ENGENHARIA ELETRICA